Analisis Segmentasi Psikografis dan Sensitivitas Harga Konsumen Rumah Makan di Kabupaten Sidoarjo - Luxi Ika Lestari; Saino Saino (BISMA (Bisnis dan Manajemen), 2018)
Now, eat not just tool to fill up a stomach. Eat have been become lifestyle together with period development and culture hase been made of human. So, restaurant necessary to do exactly segmentatiom to develop marketing strategies more exact and specific for their product target on segmen that more specific of poppulation. Psychographic segmentation is kind of segmentation that intercorrelated with individual consumers mind, by exploring such factors as value, lifestyle, and cognitive component (Lowe and Worsley,2002) In this research psycographi segmentation just use value that have 18 indicators and lifestyle that have 6 indicators (Lowe and Worsley,2002). Technique that use to taken sample is non probability sampling. To make taken saple easier, researcher use intidental sampling. Data processing technique use validitas and reliabilitas while statistic analysis use factor analysis, cluster analysis, and ANOVA analysis. Psychographic segmentation that connected with price sensitivity have 4 segment are kekanak-kanakan (1225%), alpha sosializer (23,52%), konservatif (14,21%), optimiser (26,47%), self dominance (9,80%), statis (13,72%). There is found price sensitvity different on each segment where segment stick out, alpha sosializer segment is most sensitive, just the opposite segment that have low price sensitivity are optimiser segment and self domonance segment.